The Effects of Cosmos caudatus on Structural Bone Histomorphometry in Ovariectomized Rats. (8th August 2012) - Mohamed, Norazlina; Gwee Sian Khee, Sharon; Shuid, Ahmad Nazrun; Muhammad, Norliza; Suhaimi, Farihah; Othman, Faizah; Babji, Abdul Salam; Soelaiman, Ima-Nirwana
Abstract : Osteoporosis is considered a serious debilitating disease. Cosmos caudatus ( ulam raja ), a plant containing antioxidant compounds and minerals, may be used to treat and prevent osteoporosis. This study determines the effectiveness of C. caudatus as bone protective agent in postmenopausal osteoporosis rat model. Thirty-two female rats, aged 3 months old, were divided into 4 groups. Group one was sham operated (sham) while group two was ovariectomized. These two groups were given ionized water by forced feeding. Groups three and four were ovariectomized and given calcium 1% ad libitum and force-fed with C. caudatus at the dose of 500 mg/kg, respectively. Treatments were given six days per week for a period of eight weeks. Body weight was monitored every week and structural bone histomorphometry analyses of the femur bones were performed. Ovariectomy decreased trabecular bone volume (BV/TV), decreased trabecular number (Tb.N), and increased trabecular separation (Tb.Sp). Both calcium 1% and 500 mg/kg C. caudatus reversed the above structural bone histomorphometric parameters to normal level. C. caudatus shows better effect compared to calcium 1% on trabecular number (Tb.N) and trabecular separation (Tb.Sp). Therefore, Cosmos caudatus 500 mg/kg has the potential to act as the therapeutic agent to restore bone damage in postmenopausal women.